Insignificant Response of Bacterioplankton Community to Elevated pCO2 During a Short-Term Microcosm Experiment in a Subtropical Eutrophic Coastal Ecosystem - Yang, Yunlan; Zhang, Fei; Chen, Xiaowei; Li, Huifang; Jiao, Nianzhi; Zhang, Rui (Frontiers in Microbiology, 2021)
Ocean acidification, as one of the major consequences of global climate change, markedly affects multiple ecosystem functions in disparate marine environments from coastal habitats to the deep ocean. Evaluation of the responses of marine microbial community to the increasing partial pressure of CO2 (pCO2) is crucial to explore the microbe-driven biogeochemical processes in the future ocean. In this study, a microcosm incubation of eutrophic coastal water from Xiamen Bay under elevated pCO2 (about 1000 µatm) and control (ambient air, about 380–410 µatm) conditions was conducted to investigate the effect of ocean acidification on the natural bacterioplankton community. During the 5-day incubation period, the chlorophyll a concentration and bacterioplankton abundance were not significantly affected by increased pCO2. Hierarchical clustering and non-metric multidimensional scaling analysis based on Bray-Curtis similarity among the bacterioplankton community derived from the 16S rRNA genes revealed an inconspicuous impact of elevated pCO2 on the bacterial community. During the incubation period, Proteobacteria, Bacteroidetes, Actinobacteria, Cyanobacteria and Epsilonbacteraeota were predominant in all microcosms. Despite the distinct temporal variation in the composition of the bacterioplankton community during the experimental period, statistical analyses showed that no significant difference was found on bacterioplankton taxa between elevated pCO2 and control, indicating that the bacterioplankton at the population-level were also insensitive to elevated pCO2. Our results therefore suggest that the bacterioplankton communities in the fluctuating and eutrophic coastal ecosystems appears to be adaptable to the short-term elevated pCO2.